The Experimental and Simulation Study of Selective Catalytic Reduction System in a Single Cylinder Diesel Engine Using NH3 as a Reducing Agent - Manoj Kumar Athrashalil Phaily; Sreekumar Jayachandra Sreekala; Padmanabha Mohanan (International Journal of Chemical Engineering)
Selective catalytic reduction (SCR) technology has been widely used in automotive applications in order to meet the stringent limits on emission standards. The maximum NOx conversion efficiency of an SCR depends on temperature and mass flow rate of an exhaust gas. In order to assess the suitability of Cordierite/Pt catalyst for low temperature application, an experimental work is carried out using single cylinder diesel engine for different load conditions by varying ammonia induction rate from 0.2 kg/hr to 0.8 kg/hr. The simulation is carried out using AVL FIRE for the validation of experimental results. From the study, it has been found that for 0.6 kg/hr ammonia induction rate the maximum conversion is achieved, whereas, for 0.8 kg/hr, conversion is reduced due to desorption of ammonia. Also it has been found that, at 75% of load, for all mass flow rates of ammonia the conversion was drastically reduced due to higher exhaust gas temperature and higher emission of unburnt hydrocarbons. More than 55% of NOx conversion was achieved using Cordierite/Pt catalyst at a temperature of 320°C.